Molecular mechanisms of mitochondria-mediated ferroptosis: a potential target for antimalarial interventions - Adegboro, Adegbolagun Grace; Afolabi, Israel Sunmola (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis is an iron-dependent form of regulated cell death characterized by glutathione (GSH) depletion, glutathione peroxidase 4 (GPX4) inactivation, and the build-up of lipotoxic reactive species. Ferroptosis-targeted induction is a promising therapeutic approach for addressing antimalarial drug resistance. In addition to being the primary source of intracellular energy supply and reactive oxygen species (ROS) generation, mitochondria actively participate in diverse forms of regulated cell death, including ferroptosis. Altered mitochondrial morphology and functionality are attributed to ferroptosis. Diverse mitochondria-related proteins and metabolic activities have been implicated in fine-tuning the action of ferroptosis inducers. Herein, we review recent progress in this evolving field, elucidating the numerous mechanisms by which mitochondria regulate ferroptosis and giving an insight into the role of the organelle in ferroptosis. Additionally, we present an overview of how mitochondria contribute to ferroptosis in malaria. Furthermore, we attempt to shed light on an inclusive perspective on how targeting malaria parasites’ mitochondrion and attacking redox homeostasis is anticipated to induce ferroptosis-mediated antiparasitic effects.